Social Workers’ Professional Development. Canadian Experience and Opportunities for Ukraine - Popova, Anastasiia (Universitatis Mariae Curie-Skłodowska, 2022)
The article reveals the basic principles of social workers’ professional development in Canada and identifies opportunities to use its constructive ideas in the Ukrainian practice of social work. The author analyzes the concepts of "professional development" and " social worker’s professional development". It was found that the social workers’ professional development is an important component of quality social work practice. Definitely, social workers ’professional development in Canada is the responsibility of social work professional organizations, which are divided into 2 main types: professional (government regulators at the national level, colleges and associations at the provincial and territorial levels) and educational professional organizations. The content of the main legislative documents regulating the social workers’ professional development is characterized. It was found that the basis of professional development is a program of continuous competence, which aims to promote the quality of professional activities in the field of social work and social services, as well as to encourage social workers-practitioners to constantly improve their professional skills and protect the public's right to quality services as defined in the Model Social Work Practice Act, Code of Ethics and Standards of Practice. The constructive ideas of the Canadian experience for reforming the Ukrainian system of social workers’ professional development are characterized
Keywords: Social work; social worker; professional development; continuing professional development; Social workers’ professional development; Canada